¿En qué época del año florecen las plantas de páramo? : un estudio usando datos de herbario y colecciones digitales (2020)
Colombia has 49% of the paramos globally and around 3,400 species of plants in this ecosystem. However, information and studies on the phenology of paramo plants are very scarce. For this reason, in this study we analyze the different flowering times of paramo plants based on the type of pollinator, elevation, family and their changes over time. This, through the use of digital collections such as iNaturalist and digital herbaria such as that of the National University of Colombia. It was found that there are species flowering throughout the year, but the flowering decreases in the months of July to September. Significant differences were found in the flowering season between species pollinated by wind and pollinated by animals; All year round there are species in bloom pollinated by animals, while species pollinated by wind tend to bloom less in the dry season. On the other hand, differences were found in the flowering time between the Melastomatacea family and Rosacea and Asteraceae. Finally, we did not find differences in the flowering of Espeletia grandiflora at different elevations, but there were differences in the flowering time in this century with respect to specimens of the last century.